SP0006 Visualising Crystals: DECT and More. (23rd January 2014) - Manger, B.
Abstract : The first human to see monosodium urate (MSU) crystals in his newly invented microscope was the Dutch researcher Antoni van Leeuwenhoek in 1679. Since then, the gold standard to establish the diagnosis of gout arthritis is the detection of these crystals, phagocytosed by leukocytes contained in the synovial fluid of an inflamed joint. However, various obstacles may interfere with arthrocentesis individual cases: (i) Gout patients frequently carry a high cardiovascular risk and are on anticoagulant therapy or they do not consent to an invasive procedure due to the extreme pain level of their condition. (ii) In addition, diffuse soft tissue swelling without clearly detectable effusion can make it difficult to yield sufficient material to establish diagnosis. To overcome these problems, the EULAR evidence based recommendations for gout state that "for typical presentations of gout (such as recurrent podagra with hyperuricaemia) a clinical diagnosis alone is reasonably accurate but not definitive without crystal confirmation". Musculoskeletal ultrasound has the potential to support the non-invasive diagnosis of gouty arthritis. Sonography can detect free-floating MSU crystals in synovial fluid ("snow storm appearance") or subclinical tophus deposits. The most specific ultrasonographic finding, however, is the double contour sign, representing MSU deposits on the surface of hyaline cartilage (e. g. of femoral condyles or metatarsal heads). Recently, yet another diagnostic method has been described, which allows non-invasive identification of sodium urate crystals deposits in the periarticular tissues. Dual energy computed tomography (DECT) is an imaging method, which uses X-ray beams of two different energies to differentiate solid sodium urate deposits from connective tissues and from calcium containing structures by their absorption properties. Several clinical studies could clearly demonstrate that DECT does not only reliably detect clinically overt tophi, but also detects subclinical urate deposition at periarticular or peritendinous sites in gout patients. Therefore, DECT may not only be a very helpful imaging method for tophus assessment and follow-up in clinical trials and during urate lowering therapy in patients with the established diagnosis of chronic gout. It may also be valuable as differential diagnostic tool in patients with "unclassified" acute or relapsing arthritides, when aspiration of synovial fluid is not possible or not successful. Disclosure of Interest: None Declared